Usage of Phytohormones for Aseptic Regeneration of Two Medicinal Important Plant Species, Adhatoda Vasica and Aloe Vera (International Journal of Scientific Research in Science and Technology, 2024)
Two plants species Aloe vera and Adhatoda vasica belongs to family Liliaceae (Asphodelaceae) and Acanthaceae respectively. Present study was carried out to establishment of systematics protocol for ascetic, in-vitro regeneration of these plants using different concentration of phytohormones specifically cytokinin and auxin. The experimental result indicates percentages of regeneration was maximum in MS (Murashige and Skoog) medium with combination of 3mg/l BAP and 0.75mg/l NAA in Aloe barbadensis for direct shoot induction and 4mg/l BAP with 1mg/l NAA for indirect shoot regeneration, while in Adhatoda vasica highest percentage of shoot induction observed in 1 mg/l BAP and 0.2mg/l NAA. MS medium with combination of 1mg/l IBA was found to be best for the root induction in both the plant species.